Elastic modulus of cadaveric acetabular labrum correlates with ultrashort echo time (UTE) apparent spin-spin (T2*) and spin-lattice (T1) relaxation times - Moazamian, Dina; Hananouchi, Takehito; Shaterian Mohammadi, Hamidreza; Tayarani, Alireza; Dorthé, Erik W.; D'lima, Darryl; Jerban, Saeed (Frontiers in Musculoskeletal Disorders, 2024)
The acetabulum labrum plays a critical role in hip function. Medical imaging techniques for measuring changes in labral properties due to its degeneration may help improve our knowledge of its role in hip osteoarthritis (OA).This study aimed to explore the correlation between the mechanical properties of the acetabulum labrum and ultrashort echo time (UTE) MRI properties.Material and Method: Acetabular labrum specimens were dissected from 12 fresh-frozen human cadaveric hip joints (64.6±11.6 years old at the time of death, 7 female). UTE Cones sequences were used to measure apparent spin-spin (T2*) and spin-lattice (T1) relaxation times using a knee coil at 3T in a clinical MR scanner. The stiffness and the elastic modulus (E) of the specimens were measured before MRI scans using uniaxial tensile tests. Spearman's rank correlation coefficients of UTE-T2* and -T1 with their mechanical properties of them were calculated.The human labrum specimen elastic modulus showed a significant inverse correlation with UTE-T2* (R=-0.67, P<0.05) and with UTE-T1 (R=-0.56, P=0.05). The stiffness of the specimens showed significant inverse correlations with UTE-T2* (R=-0.53, P=0.05) and UTE-T1 (R=-0.63, P=0.02).This study highlighted the potential of UTE-MRI techniques for the mechanical assessment of the acetabular labrum. UTE-MRI may improve labrum degeneration detection and monitoring, which requires further investigations.